A new agro-hydrological catchment model to assess the cumulative impact of small reservoirs. (July 2022) - Lebon, Nicolas; Dagès, Cécile; Burger-Leenhardt, Delphine; Molénat, Jérôme
Abstract: Small-reservoir development is a challenging issue in agricultural catchments facing water scarcity. An integrated, new and original agro-hydrological model considering small reservoirs, MHYDAS-Small-Reservoirs, is presented. The model explicitly represents relevant spatial scales (plot, small-reservoir, stream reach, groundwater, and catchment scales) and the agronomic and hydrological links between these scales at which agriculture-hydrology interactions occur. After numerical verification, the model is evaluated by applying it to a 19-km 2 catchment. The model satisfactorily simulates the annual stream runoff (within 6%) and daily stream runoff (Nash efficiency = 0.47) but tends to overestimate the crop yield (+21%). Simulations, one under actual basin conditions and one under virtual conditions, were carried out. This highlighted the potential of the model to predict the local and cumulative impacts of small reservoirs. Hence, MHYDAS-Small-Reservoirs is a promising model for land use planning and water management of agricultural catchments containing small reservoirs. Highlights: We present an agro-hydrological catchment model considering small reservoirs. Catchment elements (reservoir, plot, stream reach, etc.) are explicitly represented. The model satisfactorily simulates hydrological and agricultural variables and fluxes. Local and cumulative impacts of small reservoirs are simulated. One of the goals of the model is to gain insight into the causes of the impacts.